FINANCIAL DISTRESS: RASIO KEUANGAN DAN STRUKTUR KEPEMILIKAN PADA PERUSAHAAN NON-KEUANGAN - VALENTINA VALENTINA; TJHAI FUNG JIN (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2020)
The purpose of this research is to analyze if the factors in this research can influence the occurrence of financial distress. This research analyze about liquidity, leverage, profitability, firm performance, dividend policy, firm size, managerial ownership, and institutional ownership which to test how far they affected the occurrence of financial distress. Data for this research was taken from annual report of non financial companies listed in Indonesia Stock Exchange in period 2016 to 2018. This research has 49 companies that fulfilled the criteria as the final sample. Hypothesis in this research were tested by multiple linear regression analysis method. The results showed that profitabilty, firm performance, firm size, and managerial ownership that has an effect on financial distress. Besides, liquidity, leverage, dividend policy, and institutional ownership has no effect on financial distress.